Equality vs equity : tackling issues of race in the workplace - Garrett, Jenny, 1971- (Emerald Publishing, 2023)
To achieve racial equity in the workplace, we need to "name, frame and explain where it doesn't exist". In Equality vs Equity: Tackling Issues of Race in the Workplace, Jenny Garret OBE helps the reader unpack the concept of racial equity and understand its importance in moving the dial up on inclusion, providing practical tips and language for the reader to act upon. Equality vs Equity: Tackling Issues of Race in the Workplace is essential reading for those who want to educate themselves and influence others to do the crucial complex work of achieving racial equity in the workplace.